Skin mucus of Cyprinus carpio inhibits cyprinid herpesvirus 3 binding to epidermal cells. - Raj, Victor Stalin; Fournier, Guillaume; Rakus, Krzysztof; Ronsmans, Maygane; Ouyang, Ping; Michel, Benjamin; Delforges, Cédric; Costes, Bérénice; Farnir, Frédéric; Leroy, Baptiste; Wattiez, Ruddy; Melard, Charles; et al. (Vet Res, 2011)
Cyprinid herpesvirus 3 (CyHV-3) is the aetiological agent of a mortal and highly contagious disease in common and koi carp. The skin is the major portal of entry of CyHV-3 in carp after immersion in water containing the virus. In the present study, we used in vivo bioluminescence imaging to investigate the effect of skin mucus removal and skin epidermis lesion on CyHV-3 entry. Physical treatments inducing removal of the mucus up to complete erosion of the epidermis were applied on a defined area of carp skin just before inoculation by immersion in infectious water. CyHV-3 entry in carp was drastically enhanced on the area of the skin where the mucus was removed with or without associated epidermal lesion. To investigate whether skin mucus inhibits CyHV-3 binding to epidermal cells, tail fins with an intact mucus layer or without mucus were inoculated ex vivo. While electron microscopy examination revealed numerous viral particles bound on the fins inoculated after mucus removal, no particle could be detected after infection of mucus-covered fins. Finally, anti-CyHV-3 neutralising activity of mucus extract was tested in vitro. Incubation of CyHV-3 with mucus extract reduced its infectivity in a dose dependent manner. The present study demonstrates that skin mucus removal and epidermal lesions enhance CyHV-3 entry in carp. It highlights the role of fish skin mucus as an innate immune protection against viral epidermal entry.
Keywords: Animals; Carps; Cells, Cultured; DNA Virus Infections; DNA Viruses; Epidermis; Fish Diseases; Immunity, Innate; Luminescent Measurements; Microscopy, Electron, Transmission; Mucus; Virus Attachment